Arithmetic module, device and system - Liu Chih-Wei; Chang Kuo-Chiang; Ou Shih-Hao; Chen Yu-Wen (My University, 2015)
An arithmetic module is provided, including a first adder, a first shifter coupled to the first adder, a multiplier coupled to the first shifter for receiving an external coefficient signal, a digit alignment unit coupled to the multiplier, a second adder coupled to the digit alignment unit, and a second shifter coupled to the second adder. The arithmetic module reduces the overall computation time effectively, as compared with a scalar processor, by employing a serial data connection design, and also significantly reduces power consumption of the digital signal processor by requiring fewer input and output ends than those of a multi-issue processor.